2021
DOI: 10.1080/21655979.2021.2002495
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor 2 mRNA binding protein 2 regulates proliferation, migration, and angiogenesis of keratinocytes by modulating heparanase stability

Abstract: Wound healing is related to proliferation, migration, and angiogenesis of keratinocytes. Insulin-like growth factor 2 mRNA binding protein 2 (IGF2BP2) is an important N6-methyladenosine (m6A) reader, which is involved in multiple processes, including wound healing. However, the function and mechanism of IGF2BP2 in keratinocyte processes are largely uncertain. In the present study, expression levels of IGF2BP2 and heparanase (HPSE) were detected by quantitative reverse transcription polymerase chain reaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous studies have found that decreased VEGF secretion in HaCaT inhibits angiogenesis. 33 , 34 Eunah Suhng et al found that LL-37 and IL-33 enhanced VEGF mRNA expression and VEGF release in HaCaT cells. Thus, IL-33 and LL-37 may mediate the angiogenesis of rosacea skin through VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that decreased VEGF secretion in HaCaT inhibits angiogenesis. 33 , 34 Eunah Suhng et al found that LL-37 and IL-33 enhanced VEGF mRNA expression and VEGF release in HaCaT cells. Thus, IL-33 and LL-37 may mediate the angiogenesis of rosacea skin through VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration was investigated by wound healing assay according to protocols as reported previously. 27 A sterile 200 µl pipette tip was used to scrape an injured area on the monolayer in a six-well culture dish when the cells reached 80% confluence. The culture was continued in a medium supplemented with 3% FBS and 1% penicillin/streptomycin (TransGen, Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…The subgroups of the insulin‐like growth factor‐2 mRNA‐binding protein (IGF2BP) family play critical roles in embryogenesis, carcinogenesis, and chemoresistance by influencing the stability, translatability, or location of ncRNAs 96–98 . Specifically, IGF2BP2 has been identified as a pro‐tumour factor in various solid tumours 99 .…”
Section: Lncrna/mirna/mrna Networkmentioning
confidence: 99%
“…The subgroups of the insulin‐like growth factor‐2 mRNA‐binding protein (IGF2BP) family play critical roles in embryogenesis, carcinogenesis, and chemoresistance by influencing the stability, translatability, or location of ncRNAs. 96 , 97 , 98 Specifically, IGF2BP2 has been identified as a pro‐tumour factor in various solid tumours. 99 In a recent study by Xia et al., 100 it was found that IGF2BP2 levels are elevated in CRC cells and tissues compared to normal counterparts.…”
Section: Lncrna/mirna/mrna Networkmentioning
confidence: 99%